Water Solubility Enhancement of Pyrazolo[3,4-d]pyrimidine Derivatives via Miniaturized Polymer–Drug Microarrays - Sanna, Monica (ACS Med Chem Lett, 2018)
[Image: see text] A miniaturized assay was optimized to evaluate the enhanced apparent water solubility of pyrazolo[3,4-d]pyrimidine derivatives used extensively as anticancer drug scaffolds. The applied amount of drugs used in the reported strategy ranged from 5 to 10 μg per formulation which were dispensed by an inkjet 2D printer directly into a 96-well plate. The selected polymer/drug formulations with high water solubility demonstrated improved cytotoxicity against a human lung adenocarcinoma cancer cell line (A549) compared to the free drugs. We attribute the enhanced efficacy to the improved apparent-solubility of the drug molecules achieved via this methodology. This novel miniaturized method showed promising results in terms of water solubility improvement of the highly hydrophobic pyrazolo[3,4-d]pyrimidine derivatives, requiring only a few micrograms of each drug per tested polymeric formulation. In addition, the reported experimental evidence may facilitate identification of suitable polymers for combination with drug, leading to investigations on biological properties or mechanisms of action in a single formulation.